Design and comparative validation of antipodal vivaldi antenna using periodic elliptical-slots with extended triangular-shaped as dielectric lens for microwave imaging applications - Shaikh, Faraz Ahmed; Khan, Sheroz; Alam, A. H. M. Zahirul; Shahid, Zeeshan; Khan, Talha Ahmed (IEEE, 2019)
This paper presents the novel design of an ultra" #ideband (UWB) antipodal Vivaldi antenna using periodic elliptical slots (PES"AVA) for microwave and radar imaging applications. Further, the high permittivity (ɛr=10.2) dielectric lens which triangular in shaped is introduced in"!ront (PES" AVA"3) to improve the linear polarization performance, gain as well as directivity of the antenna. The antenna design and its optimization process offer good outcomes by using low"+ost substrate material, ﬁberglass reinforced grade 4 (FR4) with a thickness of 1.57mm and permittivity of (ɛr=4.3) respectively. The (PES"AVA) antenna design produces the average effects of gain (5"9dB) and directivity of (5"10dBi). However, the addition of the triangular"shaped dielectric lens placed in front of an antenna is able to improve the peak gain up to 10.6dB with 11.9dBi in directivity. The radiation patterns of the proposed antenna have been also improved by using the dielectric lens where the magnitude of the main lobe is larger than (PES"AVA). Around 2dB improvements in gain at different UWB frequency level with better directivity using the dielectric lens with antenna (PES"AVA"3) as compared to regular (PES"AVA). The dimension of the proposed antenna is 60.75mm x 66mm approximately. The designed antenna operates with in frequency range of (3GHz"to"10GHz). The structural layout and comparative validation of (PES"AVA) with or with"out dielectric lens have been certified using CST simulation software.